Tax Treatment of Debt Restructuring and Implementation of PSAK 109 - Benny Gunawan Ardiansyah (IPSAR (International Public Sector Accounting Review), 2025)
The weakening global economy since the Covid-19 pandemic have triggered a decline in corporate operating profits. Some companies enconter operational losses and the possibility of default. But, for big companies or state owned companies, bankruptcy and liquidation are not an option. Then, debt restructuring or deb modificaion is the preferred for them, allowing companies, such as PT Garuda Indonesia Tbk (GIAA) and PT Waskita Beton Precast Tbk (WSBP), continuing their operation. PSAK 109 recognizes gains and/or losses for restructuring of debt modification from short term to the long term debt. However, there are no tax regulations governing this matter. This study describes the tax treatment of unrealized gains on debt modification due to the implementation of PSAK 109. This study used qualitative methods, conducted through a literature review and in-depth interviews with tax authorities and taxpayer representatives. The results indicate that the debt restructuring undertaken by GIAA and WSBP generated profits due to the exchange of old debt instruments for new ones. Gains on modifications do not actually provide additional ability to pay. However, we must highlight that the definition of tax objects is very broad, so it is still included in the definition of PPh objects in the form of recognition of debt relief income based on Article 4 paragraph (1) letter k of the PPh Law. In addition, there is a burden on the amortization of discount interest expenses that can be charged by the creditor (banking). The addition of expenses that can be deducted as a reduction in the creditor's taxable income should be income for the debtor